USING GAMES TO SOCIALIZE PRESCHOOL CHILDREN - Xujanazarova Nargiza Mirzamaxmudovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
At an early age, children receive initial ideas of a social nature and are included in the system of social relations through solving the following tasks: development of play activities, familiarization with elementary generally accepted norms and rules of relationships with peers and adults, formation of family, and civic affiliation. Play is a source of development of the child’s consciousness, the arbitrariness of his behavior, and a special form of modeling the relationship between a child and an adult.